Investigations on thermo-mechanical properties of organically modified polymer clay nanocomposites for packaging application. Issue 8 (October 2021) - Sudhakar, YN; Selvakumar, M; Bhat, D Krishna
Eco-friendly packing polymer materials are in the spotlight but, lack of new biodegradable polymers either natural or synthetic is yet to establish the market more competitively. So, in the present work, clay as a nano-filler is embedded and organically modified in some synthetic and natural polymers which are well established commercially to enhance their biodegradability. The impact of clay on the properties of synthetic polymers namely, poly(methyl methacrylate) (PMMA), poly(vinyl chloride) (PVC), poly(vinyl acetate) (PVAc) and natural polymer cellulose acetate butyrate (CAB) was studied. Results from differential scanning calorimetric (DSC) showed a decrease in the glass transition temperature of organically modified polymer clay nanocomposites (PCC) than pure polymers. Scanning electron microscopy (SEM) displayed a uniform surface with small-sized crystallites distributed on the polymer surface. X-ray diffraction (XRD) spectra revealed the formation of enhanced intercalated structures in PCC. Furthermore, FTIR studies showed that the interlayer bonding (Si–O bands) of pure clay is deformed in PCCs. The tensile strength of PCC increased with an increase in organo-clay loading. This unique mechanical behavior is due to the agglomeration of organo-clay particles. Finally, the biodegradation studies revealed enhanced hydrolytic degradation in PCC than pure polymers. Hence, these PCCs are environmentally friendlier than their pure synthetic polymers without significant compromise in their properties, which makes it suitable for packaging industries.